Curing and subsurface damage monitoring of epoxy-based composites. (July 2019) - Fan, Gaochen; Gupta, Sumit; Loh, Kenneth J
Multifunctional fiber-reinforced polymer composites that incorporate a suite of functionalities in addition to their load-carrying capability are receiving significant attention. One approach to realize multifunctional fiber-reinforced polymers is by infusing nanomaterials in the epoxy matrix to enhance their mechanical properties and to enable sensing functionality. However, fabrication of nanomaterial-enhanced epoxies remains challenging, since additives can hinder curing and affect their mechanical properties. Therefore, the objective of this study is to employ electrical capacitance tomography for monitoring curing and for quantifying subsurface damage in nanocomposite epoxies. The vision is that electrical capacitance tomography can be used as a portable, nondestructive evaluation tool for assessing composite curing during manufacturing or in the field (e.g. for repair patches). In short, electrical capacitance tomography uses a set of noncontact electrodes arranged to form a circle and interrogates a sensing area using different patterns of electric field excitations. Boundary capacitance measurements obtained simultaneously are used as inputs for solving the electrical capacitance tomography inverse problem to reconstruct the electrical permittivity distribution of the sensing area. The hypothesis is that the permittivity of nanocomposite epoxies would change during curing and due to damage. To test this hypothesis, this work focused on carbon nanotube–based epoxies, whose electrical properties are sensitive to strain. First, high-speed shear mixing and tip sonication were employed for dispersing carbon nanotubes in epoxy resin. Specimens were fabricated to confirm their strain-sensitive electromechanical properties. Second, electrical capacitance tomography was used to monitor nanocomposite epoxy curing, and the results confirmed the hypothesis that permittivity decreased with increasing curing time. Third, these results were then validated by directly measuring their electrical permittivity changes during curing and also using ultrasonic testing to estimate its elastic modulus at different curing times. Finally, nanocomposite epoxy specimens were damaged by drilling different-sized holes, and electrical capacitance tomography was able to identify the locations and sizes of the simulated damage.